Profit shifting by debt financing in Europe - Francesca Barion; Raffaele Miniaci; Paolo M. Panteghini; Maria Laura Parisi (Center for Economic Studies and ifo Institute (CESifo), 2010)
This article aims at analyzing the link between subsidiaries' capital structure and taxation in Europe. First we introduce a trade-off model, which studies a MNCs' financial strategy and shows how debt policy allows multinational groups to shift profits from low-tax to high-tax jurisdictions. By letting the MNC choose both leverage and the percentage of profit shifting, we depart from the relevant literature which has mainly focused on the latter. Using the AMADEUS dataset we show that: i) subsidiaries' leverage increases with the statutory tax rate, levied in the country where it operates; ii) this positive effect is lower, the higher the parent company tax rate is. Furthermore, an increase in the parent company's tax rate is estimated to raise its subsidiaries' leverage.
Keywords: G31; H25; H32; 330; capital structure; default; multinationals; profit shifting; taxation; Gewinnverlagerung; Multinationales Unternehmen; Auslandsniederlassung; Fremdkapital; Kapitalstruktur; Internationale Finanzierung; Europa